Application of Nitroxide Mediated Polymerization in Different Monomer Systems - Maric, Milan (Current Organic Chemistry, 2018)
Nitroxide mediated polymerization (NMP) is one of the main reversible deactivation radical polymerization (RDRP) techniques and was one of the earliest discovered. However, other RDRP processes like atom transfer radical polymerization (ATRP) and reversible addition fragmentation transfer polymerization (RAFT) surpassed NMP, as it was largely restricted to styrenic polymerizations. Recently, with second-generation nitroxides, controlled homopolymerizations (predictable degree of polymerization with conversion, high chain end fidelity and narrow molecular weight distributions) of acrylates, acrylamides and dienes are now possible. Methacrylic ester homopolymerizations have remained somewhat elusive with commercially available alkoxyamines, but with a low concentration 1-10 mol% of a controlling co-monomer, methacrylate-rich polymers are accessible. Recent reports have shown promising possibilities for methacrylate homopolymerizations. This review will summarize the progress made in the diversity of monomers polymerizable by NMP and an outlook of the ability of NMP to polymerize new families of monomers or to use under-utilized monomers for emerging applications will be given.
Keywords: acrylamides